DUSUN EDUCATION: âSEBAGAI STRATEGI PENEKANAN TINDAK KRIMINAL MELALUI RAMBU-RAMBU MORAL DI DESA DUKUHWALUH KECAMATAN KEMBARAN KABUPATEN BANYUMAS - Janah, Felistya Aprili Baeti; Setiana, Desti Dwi; Mistialim, Balkis (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Dukuhwaluh village located in the district of Banyumas twins has a strategic location because it is close to educational facilities such as Muhammadiyah University of Purwokerto, and educational institutions at the high school, junior high, elementary and early childhood education. The number of educational facilities should be able to encourage the distribution of better science, so that science is not only channeled directly to the educational actors alone, but able to give a positive impact to the surrounding community. But in fact the people in the village Dukuhwaluh still less awareness about education. Number of children who drop out of school so that trigger high unemployment, crime often triggers. Therefore, we moved to this situation to give an effort to improve the moral crisis through the program